2009
DOI: 10.1016/j.rehab.2008.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Physical training combined with dietary measures in the treatment of adult obesity. A comparison of two protocols

Abstract: Our survey demonstrated the beneficial effect of combining dietary measures and physical training in obese patients. In addition to weight loss, the programme enabled a reduction in the patients' body fat mass and abdominal obesity, a correction of metabolic disorders and an improvement in aerobic capacity. The improvement in all these parameters also enhanced the patients' psychological status and quality of life. The addition of strength training produced notable improvements in weight loss, arm muscle stren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
2
6

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 52 publications
1
42
2
6
Order By: Relevance
“…The distance travelled in the 6 MWT has increased by 95 m for the MG and 100 m for the EG. This increase is much higher than the 56 m of increase reported by S. Ghroubi et al [53] after similar training combined with diet. Relative lower intensity and advancing subject age of S. Ghroubi et al [53] study can explain a part of differences.…”
Section: Effect Of Time-of-day Specific Obese Training On Body Composcontrasting
confidence: 58%
See 2 more Smart Citations
“…The distance travelled in the 6 MWT has increased by 95 m for the MG and 100 m for the EG. This increase is much higher than the 56 m of increase reported by S. Ghroubi et al [53] after similar training combined with diet. Relative lower intensity and advancing subject age of S. Ghroubi et al [53] study can explain a part of differences.…”
Section: Effect Of Time-of-day Specific Obese Training On Body Composcontrasting
confidence: 58%
“…This decrease show an important abdominal fat decrease when compared to results reported by K.J Melanson et al (5,3 cm) [59] and R. Ross et al (6,5 cm) [56]. And it can be considered as normal variation when compared to results reported by S. Ghroubi et al (8,8 cm) [53] and S. Ghroubi et al (10,3 cm) [55] in their combined strength and endurance training associated with diet in obese.…”
Section: Effect Of Time-of-day Specific Obese Training On Body Compossupporting
confidence: 49%
See 1 more Smart Citation
“…(Andersson et al, 1991;Stiegler & Cunliffe, 2006) Of the two interventions, energy restriction through dieting is seen as the most important factor for a change in weight with exercise making a contribution to the retention of fat-free mass and long-term maintenance of BW loss (Stiegler & Cunliffe, 2006). Previous studies have shown no differences in the BW loss between different ranges of age (Ghroubi et al, 2009) or type of treatment if diet is included, (Brochu et al, 2009; Rojo-Tirado, Benito, Atienza, Rincon & Calderon, 2013) while the sex condition has been shown as an important factor (Hagan, Upton, Wong, & Whittam, 1986) for the BW loss. Moreover, initial adiposity may impact changes in body mass after an intervention, (Forbes, 2000;Goodwin et al, 1998) as Hall (2007) stated that the person with more initial body fat has a greater fraction of their weight change attributable to changes of body fat.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these studies have indicated that possible weight loss is greater if exercise is included in the overall weight-loss program (Brochu et al 2009;Ghroubi et al 2009;Hagan et al 1986). More precisely, some of these studies have described different weight-loss tendencies with different treatments (Brochu et al 2009;Del Corral et al 2009;Larson-Meyer et al 2010), whereas others have analyzed how variables such as sex (Hagan et al 1986), psychosocial actions (Jakicic et al 2008), and lifestyle control (Redman et al 2007;Volpe et al 2008) affect weight loss.…”
Section: Introductionmentioning
confidence: 99%